Pažení stavební jámy - Šajuk, Mykola (Vysoké učení technické v Brně. Fakulta stavební, 2023)
Bakalářská práce se zabývá návrhem a statickým posouzením pažení stavební jámy realizované za účelem výstavby tunelu Homole úseku dálnice D35 Ostrov – Vysoké Mýto. Úvodní část práce shrnuje základní vstupní informace o zájmové lokalitě včetně výstupů inženýrsko-geologického průzkumu a podává přehled o možnostech zajištění stavebních jam. Stěžejní část práce popisuje navržení, posouzení a ekonomické zhodnocení třech vybraných variant pažení, následné zhodnocení výsledků výběrů té nejvhodnější varianty. Výsledná konstrukce je doplněna o výkresovou dokumentaci, která je součástí přílohy.

The bachelor's thesis describes the design and static assessment of the excavation of the construction pit realized for the construction of the Homole tunnel of the D35 Ostrov – Vysoké Mýto highway section. The introductory part of the work summarizes the basic input information about the location of interest, including the outputs of the engineering-geological survey, and provides an overview of the possibilities of securing construction pits. The core part of the work describes the design, assessment and economic evaluation of three selected variants of the stocking, subsequent evaluation of the results of the selection of the most suitable variant. The resulting structure is supplemented with drawing documentation, which is part of the annex.
Sheeting of foundation pit
Keywords: Pažící konstrukce; pilotová stěna; hřebíkovaný svah; zemní kotva; stavební jáma; statický; výpočet; návrh; posouzení; ekonomické zhodnocení; GEO5; Shoring construction; pile wall; nailed slope; ground anchor; construction pit; static calculation; design; assessment; economic evaluation; GEO5